(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Fundamental bases of creation, determining the world view o f proektantov life in general and designers in particular, are considered. Tasks are formulated, which justify Ukrainian-Russian approach in design-planning is search o f national modern form in the vsskh aspects o f her proyavlennya, including in cosmopolitan.